RECOMMENDATIONS ON THE ASSESSMENT OF HISTORICAL AND CULTURAL TOURISTIC POTENTIAL - Makhmudov Sobir Khudoyberdievich; Satorov Rizamat (Journal of Learning on History and Social Sciences, 2024)
The article provides recommendations on diversification of tourism in the national economy, rapid development of regions, creation of new jobs, increase of income and standard of living of the population, increase of investment attractiveness of the country, assessment of historical and cultural tourism potential